2018
DOI: 10.5194/amt-11-1529-2018
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian aerosol retrieval algorithm for MODIS AOD retrieval over land

Abstract: Abstract. We have developed a Bayesian aerosol retrieval (BAR) algorithm for the retrieval of aerosol optical depth (AOD) over land from the Moderate Resolution Imaging Spectroradiometer (MODIS). In the BAR algorithm, we simultaneously retrieve all dark land pixels in a granule, utilize spatial correlation models for the unknown aerosol parameters, use a statistical prior model for the surface reflectance, and take into account the uncertainties due to fixed aerosol models. The retrieved parameters are total A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…In the interests of standardization and in line with other treatments of uncertainty and error in remote sensing (e.g. Rodgers, 2000;Povey and Grainger, 2015;Loew et al, 2017;Merchant et al, 2017;Mittaz et al, 2019;von Clarmann et al, 2019), the GUM terminology is also adopted here. Terms are often used inconsistently in writing or informal conversation (in particular "error" and "uncertainty"), so to assist the reader, definitions of relevant terms are as follows (and see previously cited references).…”
Section: Terminologymentioning
confidence: 99%
“…In the interests of standardization and in line with other treatments of uncertainty and error in remote sensing (e.g. Rodgers, 2000;Povey and Grainger, 2015;Loew et al, 2017;Merchant et al, 2017;Mittaz et al, 2019;von Clarmann et al, 2019), the GUM terminology is also adopted here. Terms are often used inconsistently in writing or informal conversation (in particular "error" and "uncertainty"), so to assist the reader, definitions of relevant terms are as follows (and see previously cited references).…”
Section: Terminologymentioning
confidence: 99%
“…From the table we can see that surface concentrations of sulfate and its global burden are significantly larger in SALSA2.0 than in the previous generation model, and they are at the upper end of the estimate of Liu et al (2005). Although our simulation period is not for the same period as for ECHAM5-HAM, by Liu et al (2005) and Textor et al (2006), global sulfate emissions have been suggested to be fairly constant through 2000(Granier et al, 2011. Even larger increases between the two model generations are evident for the BC and OA burdens which are approximately 3 times higher in ECHAM-HAMMOZ-SALSA2.0.…”
Section: Discussionmentioning
confidence: 85%
“…(Bergman et al, 2012). The table also shows the global burdens for these compounds for the same three model versions together with values reported by Liu et al (2005) and Textor et al (2006). Liu et al (2005) have made a synthesis of model data and Textor et al (2006) provide the analysis of global aerosol properties in AeroCom Phase I models for the year 2000.…”
Section: (A) (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-based observation by CE-318 instruments is the traditional approach for measuring high-precision aerosol optical depth (AOD) and supports well-accepted atmospheric pollution studies but is limited by its low spatial resolution and high cost in terms of human, material, and financial resources (Che et al, 2009). Thus, satellite remote sensing, which continuously observes the Earth or atmosphere in detail, has the potential to overcome the shortcomings of ground-based observations and has previously been used to quantitatively retrieve AODs at regional and global scales (Kaufman, Tanré, et al, 1997;Kaufman, Wald, et al, 1997;Kaufman et al, 2005;Sun et al, 2017;Kumar et al, 2018;Lipponen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%